The Diversity and Activity of Flies (Diptera: Cyclorrhapha) as Forensic Indicators at Outdoor and Indoor Rat Carccasses in Dramaga, Bogor - Irwan Ismail; Yusuf Ridwan; Susi Soviana (Jurnal Riset Veteriner Indonesia (Journal of The Indonesian Veterinary Research), 2018)
This study aims to identify the diversity of flies that were caught and interacted with carcasses at the day and night. Each of the three rat carcasses (Rattus norvegicus) was placed outdoor and indoor within the campus of IPB Dramaga. The carcasses were put into a screen cage. Observation of flies was begun at 06:00 am and so on every four hours until the skeletal stage of the carcasses reached. The flies that come to the carcasses and into the screen cage were collected and identified. The decomposition of the indoor carcasses is slower than at outdoor, with the longer fresh stage. Meanwhile, post-decay stage and skeletal stage were achieved at the same time at each location. Nine spesies captured flies which are forensic indicator were Chrysomya megacephala (Fabricius), Chrysomya bezziana Villeneuve, Chrysomya rufifacies (Macquart), Chrysomya saffranea, Chrysomya spp, Lucilia spp, Sarcophaga spp, Calliphora spp and Musca domestica. C. bezziana Villeneuve and C. megacephala (Fabricius) were the dominant flies at outdoor carcasses. Meanwhile, the indoor carcasses was dominated by Lucilia spp.